Influence of family composition on academic performance - Miriã Rodrigues Garcia; Eduardo Tillmann (Revista Brasileira de Estudos de População)
Abstract This study aims to investigate the causal influence of family structure on the academic performance of 5th-grade elementary students in Brazil, while exploring additional factors that could impact this relationship. This is achieved using propensity score matching based on data from the Brazilian Basic Education Assessment System (Saeb) for 2019. The results indicate a significant positive difference in academic performance among students residing in biparental households compared to those living with a single parent. Regardless of contextual backgrounds, the positive impact on academic performance of having both parents remains consistent. An exception is observed when grandparents also live with the students. This highlights potential resource competition and socioeconomic disadvantages often associated with multigenerational households. Therefore, this study underscores the critical role of family composition in shaping school performance, emphasizing the importance of implementing strategies to mitigate the adverse effects of single-parent household structures on learning, given their potential to affect a broad spectrum of future socioeconomic outcomes.